Prevalence of acute diarrhea and water, sanitation, and hygiene (WASH) associated factors among children under five in Woldia Town, Amhara Region, northeastern Ethiopia - Weldehawariyat Getahun; Metadel Adane (BMC, 2021)
Abstract Background Diarrhea among children under five is one of the significant public health concerns in developing countries, such as Ethiopia that is mainly attributed to inadequate water, sanitation and hygiene (WASH) services. Lack of data on the prevalence and factors associated with acute diarrhea in Woldia Town impedes the effectiveness of WASH programs in the area. Therefore, the aim of this study was to investigate the prevalence and WASH-associated factors of acute diarrhea among under-five children in this area. This study will help guide local diarrhea prevention and control programs. Methods A community-based cross-sectional study was conducted among 485 children under age five from March to June 2018. The study participants were allocated proportionally and then households with children of this age group were selected from each kebele (the smallest administrative unit in Ethiopia) using a systematic random sampling technique. Data were collected from mothers/caregivers of the under-five children using a structured questionnaire and on-the-spot observation checklist. A binary logistic regression model with 95 % CI (confidence interval) was used to measure the association between dependent and independent variables. From the multivariable analysis, variables with a p-value < 0.05 were taken as factors significantly associated with acute diarrhea among under-five children. Results The prevalence of acute diarrhea among the children was 17.6 % (95 % CI: 14.2-21.0 %). Almost two-thirds 307 (63.4 %) of study participants' main source of drinking water was a private tap; 320 (66.1 %) of households used less than 20 l per capita per day. About one-fifth 99 (20.5 %) of households used an improved sanitation facility. Only one-fifth (21.1 %) of the latrines had nearby handwashing facilities. Less than half 225 (46.5 %) of mothers/caregivers had good handwashing practice at critical times. Water consumption of less than 20 l per capita per day (adjusted odds ratio [AOR] = 2.45; 95 % CI: 1.36-5.84), unimproved sanitation facility (AOR = 3.57; 95 %CI: 1.64-6.51), practicing unsafe child feces disposal (AOR = 2.51; 95 % CI: 1.69-4.64), poor handwashing practice at critical times (AOR = 1.85; 95 % CI: 1.34-3.56) and having no information about diarrhea being prevented by handwashing with water and soap (AOR = 3.12; 95 % CI: 1.64-6.27) were significantly associated with acute diarrhea. Conclusions More than one in six children under age five had acute diarrhea, a proportion that could be considered relatively high. We recommend that government organizations and concerned stakeholders strengthen urban WASH programs to focus on increasing the availability of sufficient water for adequate daily consumption, and promote safe disposal of child feces and good handwashing practices at critical times. Further effort is needed to sensitize mothers/caregivers about diarrhea prevention through effective WASH activity to reduce the burden of this problem among children under five.